Analysis of the knowledge of zoonotic diseases held by students associated with the Health Chair, ECEN-UNED, Costa Rica (Revista Electrónica Calidad en la Educación Superior, 2025)
Zoonotic diseases, also known as zoonoses, are infectious diseases caused by various etiological agents that can be transmitted between animals and humans. These diseases are of great importance in public health, and their occurrence has increased in recent years. In response to this complex panorama, the “One Health” approach emerged, offering a more holistic view of health. To contribute to the education of professionals trained under this approach, the Health Department at the School of Exact and Natural Sciences of the National Distance Education University (UNED) undertook an analysis of educational needs related to zoonotic diseases among the students they serve. Out of a total of 1989 students from different majors enrolled in courses offered by the Health Department between November 2022 and August 2023, a participation rate of 10% was obtained. Most participants were enrolled in majors such as Health Services Administration and Health Records and Statistics. Overall, there are information gaps related to various aspects of the zoonotic disease theme, particularly concerning transmission mechanisms, causes and consequences, prevention, impacts, and the current state of these diseases at the national level. These information gaps have been categorized into seven thematic areas, forming part of the action plan currently being developed. The need for well-prepared healthcare professionals in the field of zoonoses is essential to comprehensively address these increasingly frequent diseases that pose risks to human, animal, and ecosystem health.
Keywords: Zoonoses; One health; Knowledge; University students